2023
DOI: 10.13057/biodiv/d240145
|View full text |Cite
|
Sign up to set email alerts
|

The fate of mangrove ecosystem sustainability on the shrimp cultivation area in Tulang Bawang District, Lampung, Indonesia

Abstract: The exploitation of mangrove forests for economic purposes is rampant in tropical countries nowadays, particularly for shrimp farming, such as in the Lampung green belt in the front of the Java Sea. So, ensuring the sustainability of existing mangroves is the need of the hour. In view of above, this study aims to analyze the sustainability index of mangrove ecosystem management and the sustainability status of the mangrove ecosystem from the ecological, economic, social, and institutional dimensions using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Pokmaswas officers will release some of the hatchlings that have successfully hatched and leave some of the hatchlings for conservation. The sustainability status of the Kili Kili Park coastal turtle conservation area was carried out using Rapfish analysis using six dimensions, namely the ecological dimension, social dimension, institutional dimension, ethical dimension, and infrastructure dimension (Bakri et al, 2023). From each dimension, several attributes are measured (quantitative and qualitative), and then weighted using Multidimensional Scaling (MDS) and analyzed using Rapfish software.…”
Section: Release Of Hatchlings In the Seamentioning
confidence: 99%
“…Pokmaswas officers will release some of the hatchlings that have successfully hatched and leave some of the hatchlings for conservation. The sustainability status of the Kili Kili Park coastal turtle conservation area was carried out using Rapfish analysis using six dimensions, namely the ecological dimension, social dimension, institutional dimension, ethical dimension, and infrastructure dimension (Bakri et al, 2023). From each dimension, several attributes are measured (quantitative and qualitative), and then weighted using Multidimensional Scaling (MDS) and analyzed using Rapfish software.…”
Section: Release Of Hatchlings In the Seamentioning
confidence: 99%
“…The location selection was based on the consideration that a mangrove forest directly opposite the East Coast is used for various purposes, but spatial information on changes in density and area is still limited. The mangrove ecosystem in Tulang Bawang District, Lampung Province is one mangrove habitat that is now being damaged and needs special attention (Bakri et al 2023). The area has long been used for the aquaculture sector, especially shrimp ponds, which has implications for changes in the ecological system of the local area.…”
Section: Study Areamentioning
confidence: 99%
“…Therefore, continuous monitoring is required to detect threats to the mangrove ecosystem to optimize the use of coastal areas for shrimp farming without any compromising environmental quality deterioration (Bakri et al 2023). Monsef and Smith (2017) revealed that mangrove monitoring is needed to measure growth rates and identify improvement areas.…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations